Sustained censorship in BH (2026-05) (Bahrain) - Voidly (2026)
CRITICAL severity censorship detected in Bahrain. Confidence: 85%. Data sourced from OONI.
Censorship Incident ID: BH-2026-0103
Keywords: censorship; BH; censorship; critical